Public Health Genomics European Network: Report from the 2nd Network Meeting in Rome (Italian Journal of Public Health, 2007)
Dear Sirs,The Public Health Genomics European Network (PHGEN) is a mapping exercise for the responsible and effective integration of genome-based knowledge and technologies into public policy and health services for the benefit of population health. In 2005, the European Commission called for a “networking exercise…to lead to an inventory report on genetic determinants relevant for public health”[1], this lead to the funding of a PHGEN three year project (EC project 2005313).This project started in early 2006 with a kick-off meeting in Bielefeld / Germany.The project work is comprised of, according to the public health trias, three one year periods of assessment, policy development and assurance.At the end of the assessment phase a network meeting was held in Rome from January, 31st to February 2nd 2007 with over 90 network members and network observers in attendance. The participants represented different organisations throughout the European Union with expertise in areas such as human genetics and other medical disciplines,epidemiology,public health, law, ethics, political and social sciences. The aim of the meeting was to wrap up the last year’s assessment period and to herald the policy development phase.The assessment period of PHGEN was characterised by several activities: - Contact and cooperation with other European and internationally funded networks and projects on public health genomics or related issues (e.g. EuroGenetest, EUnetHTA, Orphanet, IPTS, PHOEBE, GRaPHInt, P3G) - Identification of key experts in public health genomics in the European members states, applicant countries and EFTA/EEA countries from different disciplines (e.g. human genetics and other medical disciplines, public health, law, philosophy, epidemiology, political and social sciences) - Building up national task forces on public health genomics in the above mentioned countries - Establishing and work in three working groups: public health genomics definitions, genetic exceptionalism and public health genomics issues and priorities - Participation in the development process on OECD and European Council documents on genetic testing - Dissemination of results in journals, on websites and in conferences.